Fear of a Black planet: Climate apocalypse, Anthropocene futures, and Black social thought - Davidson, Joe P.L. (2021)
In recent years, images of climate catastrophe have become commonplace. However, Black visions of the confluence of the Anthropocene and the apocalypse have been largely ignored. As we argue in this article, Black social thought offers crucial resources for drawing out the implicit exclusions of dominant representations of climate breakdown and developing an alternative account of the planet’s future. By reading a range of critical race theorists, from Frederick Douglass and W. E. B. Du Bois to Octavia Butler and Ta-Nehisi Coates, we propose a rethinking of the climate apocalypse. The African American theoretical and cultural tradition elaborates an image of the end of the world that emphasises the non-revelatory nature of climate catastrophe, warns against associating collapse with rebirth, and articulates a mode of maroon survivalism in which the apocalypse is an event to be endured and escaped rather than fatalistically expected or infinitely delayed.